Kajian Matematis Mengenai Strategi Pengembangbiakan Sapi Potong Lokal Guna Meningkatkan Kualitas Daging Sapi - Hidayat, Zaki Maulana; Andzar Tsaqif Laksana; Anita Triska (UNIB Press, 2023)
Beef is one of the most demanded food products in Indonesia compared to other meat commodities. The high demand of this commodity causes a shortage of its supply so that the government has to import it from other countries. As the consequences, people in Indonesia prefer to consume imported beef rather than local beef, especially those in the food industry, since imported beef has better quality. Thus, government may establish a program that is able to increase the local beef quality thereby increasing its competitiveness, for instant by cross-breeding of local and imported cattle. This paper is to discuss a cross-breeding simulation to predict the distribution of offspring produced in the next few generations through mathematical approach. Simulations are conducted by following the X-Linked Inheritance concept and algebra. Simulations are carried out by three different scenarios which consider gender of the imported cattle. The simulations show that all scenarios are able to produce local cattle offspring with imported quality. However, the offspring from the cross-breeding still preserve cattle with original local genetic with a different ratio between the first and the second scenario.